PENERAPAN PERMAINAN LARI ESTAFET SEBAGAI SARANA PENINGKATKAN KEBUGARAN JASMANI SISWA YAYASAN PENDIDIKAN HKBP PADANG BULAN - Sitinjak, Feronika; Sinaga , Rismawati Veronika; Hutabarat , Nilla Wanni; Barus , Meylin Cinta BR; Sembiring, Heka Maya Sari Br (PUAN INDONESIA, 2025)
Education is a lifelong process that shapes students by providing role models, encouraging willpower, and fostering creativity through learning. It carries pedagogical aims and is incomplete without Physical Education (Penjasorkes), which serves as a foundation for understanding oneself and the world in line with the times. To enhance motivation and enjoyment in Penjasorkes, teachers must creatively adapt sports activities to students’ characteristics through modified games. Such learning processes are expected to lead to behavioral improvements seen in learning outcomes. Creativity is vital in developing elementary students’ potential. One effective strategy is using relay games. This community service aimed to explore relay games as a means to enhance student creativity and physical fitness. The activity involved 15 students divided into three groups in a field demonstration. Relay games were found to improve physical attributes such as strength, speed, agility, and flexibility, while also fostering teamwork and creativity.